2020
DOI: 10.12968/bjhc.2019.0055
|View full text |Cite
|
Sign up to set email alerts
|

Logical goal-setting frameworks for leprosy projects

Abstract: Background/aims Goal setting is a fundamental practice in the effective management of healthcare services worldwide. This study investigated the extent to which leprosy goal formulation in Nigeria is logical and SMART. Methods Document review of baseline problems, goal statements and goal attainments for 2016 in six leprosy projects using a customised logical framework matrix. Results A total of 15 main problems, 6 aims, 19 objectives and 42 indicators were found. The goals were problem-based and logically lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…The conceptualization of this study was informed by two theories: Lo Locke and Latham's Goal-setting Theory and the Theory of Constraints (ToC) [34][35][36]. The two theories informed identification of the research gap, the setting of research questions and objectives, and the development of an interview guide for data collection.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…The conceptualization of this study was informed by two theories: Lo Locke and Latham's Goal-setting Theory and the Theory of Constraints (ToC) [34][35][36]. The two theories informed identification of the research gap, the setting of research questions and objectives, and the development of an interview guide for data collection.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…Based on the latter, recent studies by the same author found that neither the frameworks of health objectives published as SMART by major international health organisations nor the frameworks of objectives in the project plans of a national leprosy organisation had the complete and right set of components to be SMART. 9,16 This suggests there is a dearth in the knowledge of the appropriate frameworks for setting SMART goals in health organisations globally. The extent to which existing goal-setting theories and frameworks are workable in the actual practice contexts of health organisations is therefore doubtable.…”
Section: Highlightsmentioning
confidence: 99%
“…Arguing against the inclusion of an assigned performer in a regular SMART objective statement, Ogbeiwi 15 reduced the number of essential goal components to four: outcome, indicator, target, and timeframe. Based on the latter, recent studies by the same author found that neither the frameworks of health objectives published as SMART by major international health organisations nor the frameworks of objectives in the project plans of a national leprosy organisation had the complete and right set of components to be SMART 9,16 . This suggests there is a dearth in the knowledge of the appropriate frameworks for setting SMART goals in health organisations globally.…”
Section: Introductionmentioning
confidence: 99%